P523 Improvement of quality of life and continence in patients with distal ulcerative colitis treated by mesalazine: QUARTZ study. (15th January 2020) - Paupard, T; Gonzalez, F; Siproudhis, L; Peyrin-Biroulet, L
Abstract: Background: There is no robust data which analysed quality of life, functional disability and continence of patients with distal UC. QUARTZ is the first prospective study in this situation. Methods: Observational, prospective and multicentric study involving public and private French gastroenterologist to recruit patients with mild to moderate (Mayo score ≥ 3 and ≤ 10) active proctitis or proctosigmoiditis (<20 cm) and under mesalazine for induction treatment. The patients followed for 12 months (±2 months). The primary objective was the quality of life evaluated by Short Inflammatory Bowel Disease (SIBDQ) at 8 weeks (±4 months). The functional disability and incontinence have been evaluated by IBD-Disability Index and Cleveland questionnaires. Results: From December 2015 to November 2016, 117 patients were recruited. Data of 93 patients have been analysed and results are reported on Table 1. Among the 93 patients, 75 (81%) reached a clinical remission at week 8 with a SIBDQ score improvement of 6.7 ± 7.1 point ( p < 0, 001). Treatment adherence during the induction period was non-compliance for 76 patients (81%): 17 (18%) patients stopped treatment before W8 (all those patients received rectal formulation). After induction treatment, 72 (77%) patients received maintenance treatment. 11 (12%) patients reported adverse event not linked to the treatment. Conclusion: For patients with distal ulcerative colitis treated by mesalazine, quality of life, functional disability and continence have been improved at 8 weeks of treatment despite a poor adherence.